2012
DOI: 10.1108/02635571211193644
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing, job attitudes and organisational citizenship behaviour

Abstract: Purpose-There are very few studies on the impact of job attitude on knowledge sharing. The purpose of this paper is to examine the effects of job involvement, job satisfaction, organisational commitment, and organisational citizenship behaviour (OCB) on employees' knowledge sharing behaviour. Design/methodology/approach-This research is based on a survey of 116 Information Systems personnel in Malaysia. Structural equation modelling is used to test the hypothesis. Findings-The results show that job involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
121
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 84 publications
(119 reference statements)
18
121
2
1
Order By: Relevance
“…However, there are facts that people are reluctant to share knowledge because of some workers are interested to share their knowledge, while some of them seem uninterested to share knowledge, mostly when their mistakes are not tolerated by organization (Teh and Sun, 2012;Hendriks, 1999). According to Martin (2005), diverse cultures, lack of trust, lack of time, ineffective communication and poor knowledge can prevent knowledge sharing from happening.…”
Section: Knowledge Sharingmentioning
confidence: 91%
“…However, there are facts that people are reluctant to share knowledge because of some workers are interested to share their knowledge, while some of them seem uninterested to share knowledge, mostly when their mistakes are not tolerated by organization (Teh and Sun, 2012;Hendriks, 1999). According to Martin (2005), diverse cultures, lack of trust, lack of time, ineffective communication and poor knowledge can prevent knowledge sharing from happening.…”
Section: Knowledge Sharingmentioning
confidence: 91%
“…Job satisfaction and knowledge-sharing behavior. Teh and Sun (2012) in his research revealed that job satisfaction is positively related to knowledge-sharing behavior of employees. Pascoe et.…”
Section: Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%
“…As suggested by Somech &Drach-Zahavy, (2000 cited in Oplatka, andStundi, 2010) that OCB first two dimensions was positively and significantly influences Job satisfaction. However Teh & Sun (2011) have found that OCB was not a significant mediator with Job satisfaction. With reference to the above Table 7, the adjusted r square is (0.802).This indicates that 80% of the variation in the dependent Variable (Job commitment) is explained by the Independent Variable of OCB dimensions (Altruism, Conscientiousness and Civic virtue) and the rest of the overall Job Satisfaction variance can be attributed to other factors which are held constant.…”
Section: Regression Analysismentioning
confidence: 78%